Towards teleconsultations in the metaverse: design and preliminary study of an immersive teleclinic for neuro-psychological assessment - Prié, Yannick; Vigier, Toinon; Acier, Didier; Bonneville, Hélène; Georges, Manon; Thévenet, Solène; Bulteau, Samuel (Frontiers in Virtual Reality, 2025)
Virtual Reality (VR) and Metaverse technologies open new avenues for telemedicine, particularly for teleconsultations. Our goal is to explore how these remote medical interactions can take place within immersive teleclinics. Neuropsychological testing in VR is especially promising for diagnosing and monitoring cognitive disorders. This study presents our overall approach to immersive teleclinics and the development of a social VR platform for conducting such assessments. The application enables clinicians to perform remote testing sessions that begin in a virtual waiting room and continue with a combination of clinician-guided desk-based tasks and independent test activities. Clinicians can monitor patient performance in real time through dedicated dashboards. We evaluated the system with healthy participants (pseudo-patients) and clinicians using standard measures of usability (SUS), presence (MPS), and acceptability (UTAUTQ). Initial results indicated good usability, a strong sense of presence, and high acceptability among pseudo-patients. Clinicians were more hesitant, citing usability issues, uncertainty about the clinical validity of VR-based tests, and concerns about avatar quality for psychological interviews. We discuss our design choices, the potential of our prototype for remote cognitive assessment, and broader lessons learned for teleclinics in the Metaverse. While challenges remain, our work highlights the promise of such immersive teleclinics for future medical practice.